New imine compounds and their copper complexes: synthesis, characterization and comparative investigations of morphologic, mesomorphic, thermotropic, thermo-optical and thermodynamical properties - Yorur, Cigdem; Nesrullajev, Arif; Eran, Belkiz Bilgin (TAYLOR & FRANCIS LTD, 2007)
Investigations of the morphologic, mesomorphic, thermotropic, thermo-optical and thermodynamical properties of new imine compounds and their copper complexes, synthesized by our group, have been carried out. Temperature transformations of typical textures for mesophases, taking place in imine compounds and copper complexes, and the peculiarities of the biphasic regions at the direct and reverse mesophase-isotropic liquid and isotropic liquid-mesophase phase transitions have been investigated.
Keywords: imine compounds; copper complexes; thermal properties; phase transitions; SALICYLALDIMINE SCHIFF-BASES; ISOTROPIC PHASE-TRANSITION; LIQUID-CRYSTALS; HOMOLOGOUS SERIES; MAGNETIC-FIELD; LANDAU MODEL; BEHAVIOR; MESOPHASES; DERIVATIVES; FILMS; Chemistry; Physics